Understanding the Basics of Linear Endoscopic Ultrasound: A Step-by-Step Guide to Anatomy and Orientation - Chavan, Radhika; Quintini, Dario; Gandhi, Chaiti; Giri, Suprabhat; Nabi, Zaheer; Lakhtakia, Sundeep; Rajput, Sanjay (Journal of Digestive Endoscopy, 2025)
Linear endoscopic ultrasound (EUS) has evolved into an essential modality for diagnostic and therapeutic gastrointestinal interventions. Despite its growing utilization, the learning curve for mastering linear EUS remains steep, largely due to the complexity of anatomical orientation and image interpretation. This article provides a systematic, step-by-step approach to understanding the basics of linear EUS, focusing on spatial anatomy and procedural technique. Core topics include image orientation, in vivo scope rotation with the “rule of 360,” organ and structure tracing, understanding EUS scanning planes, and a station-wise evaluation strategy. A structured checklist is proposed to enhance procedural quality and prevent anatomical oversight. Additionally, the manuscript emphasizes the often-overlooked aspect of image optimization, detailing key parameters such as frequency, gain, contrast, focus, and Doppler techniques. The article aims to demystify orientation and facilitate accurate structure identification through a systematic approach. The comprehensive yet practical framework outlined in this manuscript is designed to support both novice endosonographers in achieving procedural proficiency. Integrating these fundamental principles into routine EUS practice can enhance overall understanding of the linear EUS, and likely to reduce the learning curve.
Keywords: echoendoscope; endoscopic ultrasound; anatomy; orientation; station-wise approach